Plant Breeding Through Protoplast Fusion - Devi Armita (Universitas Andalas, 2020)
Protoplast culture (protoplast fusion) is one method of tissue culture that is widely used in plant breeding programs in a relatively short time. This method is used to overcome the problem of plants that are difficult or impossible to cross conventionally as well as used for species improvement by transferring the desired gene from the donor plant to the target plant via protoplast fusion. Protoplast fusion makes it possible to produce plants that are resistant to a disease and various abiotic stresses, rapid growth rates and have a better quantity and quality of metabolites than their parents. Various factors affect the success of fusion and regeneration of protoplasts into whole plants, including the source of explants, the composition of the enzyme solution and the duration of incubation, fusagen type and culture media for regeneration.